Community Empowerment With the Utilization of Yards For Grape Cultivation Using Biochar Mixed Media In Covid-19 Pandemic - Susila Herlambang; Danang Yudhiantoro; Astrid Wahyu Adventri Wibowo (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2022)
Background: The social economic impact of the Covid-19 pandemic was felt by all levels of Indonesian society, especially the people in Mayungan, Potorono Village, Bantul Regency. Currently, compost houses and waste banks have been formed from the collection of household waste in RT 04 and RT 05 with a capacity of 1.5 tons per week. Community service activities were carried out in the form of using the yard for grape cultivation with mixed media of biochar. Mixed media technology is expected to increase the efficiency of agricultural costs and productivity of grape cultivation.   Contribution: Seeing the great potential of Mayungan and as an effort to improve the psychological aspects of the community due to the Covid-19 pandemic, community service activities were carried out using the yard for grape cultivation with biochar mixed media. Method: The approach method used is the method of active community participation. Results: The implementation of the Internal Community Service program uses the lecture, discussion, practice, mentoring and technical guidance methods. Community service activities can be carried out properly and have the expected impact. Conclusion: Community service activities can be carried out properly. The empowerment program in the midst of the ongoing COVID-19 pandemic can relieve the mental burden of the community psychologically to strengthen the body's resistance to virus attacks through plant care every time